2018
DOI: 10.1111/cei.13208
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacology of alemtuzumab, an anti-CD52 immunomodulator, in multiple sclerosis

Abstract: SummaryAlemtuzumab, a humanized anti‐CD52 monoclonal antibody, is approved for treatment of relapsing multiple sclerosis (MS). In the Phase II/III trials, patients received 12 or 24 mg/day of alemtuzumab in two treatment courses (5 days for course 1 and 3 days for course 2), 12 months apart. Serum concentrations of alemtuzumab peaked on the last day of dosing in each course and mostly fell below the limit of quantitation by day 30. Alemtuzumab rapidly depleted circulating T and B lymphocytes, with the lowest o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 52 publications
6
80
1
1
Order By: Relevance
“…By comparison, CD52 encodes a membrane glycoprotein present at varying levels on the surface of various leukocytes but not hematopoietic cells 21 . In addition, alemtuzumab is a monoclonal anti-CD52 (αCD52) antibody that results in preferential and prolonged depletion of circulating T and B cells 22,23 and is FDA approved for the treatment of B-cell chronic lymphocytic leukemia [24][25][26] and relapsing remitting multiple sclerosis [27][28][29] . Because of its biological role in immune cells relevant to asthma as well as its potential translational implications, we, therefore, prioritized CD52 as a strong causal positional candidate gene for functional validation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…By comparison, CD52 encodes a membrane glycoprotein present at varying levels on the surface of various leukocytes but not hematopoietic cells 21 . In addition, alemtuzumab is a monoclonal anti-CD52 (αCD52) antibody that results in preferential and prolonged depletion of circulating T and B cells 22,23 and is FDA approved for the treatment of B-cell chronic lymphocytic leukemia [24][25][26] and relapsing remitting multiple sclerosis [27][28][29] . Because of its biological role in immune cells relevant to asthma as well as its potential translational implications, we, therefore, prioritized CD52 as a strong causal positional candidate gene for functional validation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These findings not only point to a novel pathway for development of asthma but may also have potential translational implications. For example, we demonstrated that treatment of mice with an α CD52 antibody mimicked the immune cell-depleting activity of alemtuzumab in the circulation in humans 33,34 . We readily observed depletion of immune cells in spleen, which in mice is considered as accurately reflecting the pool of peripheral immune cells 64 .…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, CD52 encodes a membrane glycoprotein present at high levels on the surface of various immune cells, including lymphocytes, monocytes, and dendritic cells. In addition, alemtuzumab is a monoclonal anti-CD52 (αCD52) antibody that results in preferential and prolonged depletion of circulating T and B cells 33,34 and is FDA approved for the treatment of relapsing remitting multiple sclerosis [35][36][37] and B-cell chronic lymphocytic leukemia [38][39][40] . Because of its biological role in immune cells relevant to asthma as well as its potential translational implications, we therefore prioritized CD52 as a strong causal positional candidate gene for functional validation (Fig.…”
Section: Enrichment Of Asthma-associated Variants In Regulatory Elemementioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, Immunology and our sister journal Clinical and Experimental Immunology are strongly committed to publishing high-quality research relating to new therapeutics [9][10][11][12][13][14][15][16] as well as to the provision of educational resources, and therefore we recommend the GtoImmuPdb database as a novel tool to accelerate research, education and drug discovery in immunology, infection and inflammation.…”
Section: Discussionmentioning
confidence: 99%